Multi-motif dendrons and their supramolecular structures and uses thereof - MANNING Alanna Margaret; TILSTRA Grayson; KHAN Omar Fizal; COUTURE-SEN?CAL Julien; LAU Yan Ming Anson (2024)
The present application includes dendrons of Formula I, compositions comprising these dendrons and uses thereof, in particular for the delivery of agents such as nucleic acids and drugs to cells and subjects.wherein each Repeating Group is the same or different.